Predictors of COVID-19 Infection: A Prevalence Study of Hospitalized Patients. (13th October 2021) - Tu, Huilan; Zhao, Hong; Su, Junwei; Wu, Wenrui; Xu, Kaijin; Hu, Jianhua; Zhang, Xuan; Yang, Meifang; Sheng, Jifang
Abstract : Aim . To find the predictors of coronavirus disease 2019 (COVID-19) in hospitalized patients. Methods . A prevalence study compared the characteristics of COVID-19 patients with non-COVID-19 patients from January 19, 2020, to February 18, 2020, during the COVID-19 outbreak. Laboratory test results and pulmonary chest imaging of confirmed COVID-19 and non-COVID-19 patients were collected by retrieving medical records in our center. Results . 96 COVID-19 patients and 122 non-COVID-19 patients were enrolled in this study. COVID-19 patients were older (53 vs. 39; P < 0.001) and had higher body mass index (BMI) than non-COVID-19 group (24.21 ± 3.51 vs. 23.00 ± 3.27, P = 0.011); however, differences in gender were not observed between the two groups. Logistic regression analysis showed that exposure history (OR: 23.34, P < 0.001), rhinorrhea (odds radio (OR): 0.12, P = 0.006), alanine aminotransferase (ALT) (OR: 1.03, P = 0.049), lactate dehydrogenase (LDH) (OR: 1.01, P = 0.020), lymphocyte (OR: 0.27, P = 0.007), and bilateral involvement on chest CT imaging (OR: 23.01, P < 0.001) were independent risk factors for COVID-19. Moreover, bilateral involvement on chest CT imaging (AUC = 0.904, P < 0.001) had significantly higher AUC than others in predicting COVID-19. Conclusions . Exposure history, elevated ALT and LDH, absence of rhinorrhea, lymphopenia, and bilateral involvement on chest CT imaging provide robust evidence for the diagnosis of COVID-19, especially in resource-limited conditions where nucleic acid detection is not readily available.